Asuhan Keperawatan Anak Pada An. F Dengan Gangguan Sistem Pernafasan : Faringitis Akut Di Ruang Anggrek 1 RSUD dr. Soeselo Kabupaten Tegal - Clarissa Maulidina; Esti Nur Janah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Acute pharyngitis is an inflammation of the pharynx caused by viral or bacterial infections, frequently resulting in sore throat, fever, and dysphagia. This condition is among the most prevalent acute respiratory tract infections in children and adolescents worldwide, contributing significantly to morbidity and the burden of healthcare services. Objective: This case study aimed to describe the comprehensive nursing care provided to patient An. F with acute pharyngitis at Ward Anggrek 1, RSUD dr. Soeselo, Tegal Regency. Methods: A descriptive study design with a nursing process approach was employed. Data were collected through anamnesis, physical examination, observation, and documentation review. The nursing process encompassed assessment, nursing diagnosis, intervention planning, implementation, and evaluation. Results: Assessment revealed chief complaints of throat pain (NRS scale 5), fever (38.8°C), erythematous tonsils, and nutritional deficit. Three nursing diagnoses were established: acute pain related to physiological injury, hyperthermia related to disease process, and knowledge deficit related to insufficient information exposure. Interventions included pain management, hyperthermia management, and health education. Following two days of nursing care, the patient’s condition significantly improved, with pain scale reduced from 5 to 3 and body temperature normalized to 37.7°C. Conclusion: Comprehensive nursing care incorporating pharmacological and non-pharmacological approaches effectively reduced pain and fever, and improved patient and family health literacy regarding acute pharyngitis.